Baillon's Crake Zapornia pusilla Pallas, 1776 (Aves: Gruiformes: Rallidae), a new bird species for Serbia - Dozsai Jozef; Szekeres Otto; Rajković Draženko Z. (Kragujevac Journal of Science)
During the long-term effort of the bird migration study, a single adult male Baillon's Crake Zapornia pusilla Pallas, 1776 was captured and ringed on August 8, 2018, at Ludaš Lake, near Hajdukovo village (Subotica municipality, Northern Serbia). This record represents the first confirmed occurrence of this water-dwelling species for Serbia.